MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJARPEMECAHAN SOAL CERITA BILANGAN BULAT MATEMATIKA SISWATUNARUNGU - AYU DEWAYANI, DIAN (Jurnal Pendidikan Khusus, 2016)
Abstract The cognitive development of hearing impairment children was influenced so much by the language development. The minimum language skill could influence the hearing impairment children in learning mathematics especially related with story exercise material which demanded the students to think abstractly. TTW was learning model which was begun from the activity of thinking, talking (communicating), and writing.  This research purpose was to analyze the influence of TTW learning model toward the learning result of story exercise solution of mathematics round numbers to hearing impairment students. The subject was class IV hearing impairment students in SLB-B Dharma Wanita Sidoarjo, 6 students. This research used quantitative research method with Pre-Experimental arrangement with One Group Pretest-Posttest Design. The data was collected using test technique. The data analysis technique used was statistic non parametric with Wilcoxon Two Sample Test formula. The research result indicated that the average value of pretest result was 42 and the average value of postest was 82,5. The result of data analysis indicated that α value = 0,05 and U table 5% = 0,021, so the interpretation was α > U tabel. It could be concluded that Ha was accepted, it meant that there was influence of think talk write (TTW) learning method toward the learning result of story exercise solution of mathematics round numbers to hearing impairment students. Keywords: Think Talk Write (TTW), story exercise solution